Enhancing lipid nutritional quality of oysters by hybridization between Crassostrea gigas and C. angulata. (26th September 2019) - Tan, Kar Soon; Zhang, Hongkuan; Liu, Hongxing; Cheng, Dewei; Ye, Ting; Ma, Hongyu; Li, Shengkang; Zheng, Huaiping
Abstract: In the present study, hybrid and inbred oysters were produced by factorial hybridization between two closely related species, the Pacific oyster Crassostrea gigas and the Portuguese oyster C. angulata . Tissues samples were used for the analysis of total lipid content (TLC) and fatty acid composition (FAC). In general, FAC but not TLC in hybrid oysters was significantly different from inbred oysters. Hybrid oysters have significantly lower ∑SFA composition but higher ∑PUFA composition than inbred oysters, with heterosis for ∑SFA, ∑MUFA and ∑PUFA of −6.03%, −6.53% and 14.31% respectively. Moreover, hybrid oysters have significantly higher EPA + DHA content and n3/n6 PUFA ratio than inbred oysters, indicating higher lipid nutritional quality than inbred oysters. Among them, the hybrid ♀ C. gigas × ♂ C. angulata appears to be the most nutritious. These results indicated that the lipid nutritional quality of oysters can be improved by hybridization.